1999
DOI: 10.1017/s0022112098004054
|View full text |Cite
|
Sign up to set email alerts
|

Insoluble surfactants on a drop in an extensional flow: a generalization of the stagnated surface limit to deforming interfaces

Abstract: A drop in an axisymmetric extensional ow is studied using boundary integral methods to understand the effects of a monolayer-forming surfactant on a strongly deforming interface. Surfactants occupy area, so there is an upper bound to the surface concentration that can be adsorbed in a monolayer, Γ∞. The surface tension is a highly nonlinear function of the surface concentration Γ because of this upper bound. As a result, the mechanical response of the system varies strongly with Γ for realistic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(116 citation statements)
references
References 23 publications
8
108
0
Order By: Relevance
“…This is in correspondence with the results obtained in ͑sub-͒critical flow by Hu and Lips, 8 Janssen et al, 10,13 Eggleton et al, 12 and Velankar et al 14 It remains to be seen, however, whether this should be attributed to the change in ‫*⌫ץ/*ץ‬ around the reference concentration, or due to the proximity of ⌫ ϱ * . Therefore, these cases will be considered separately.…”
Section: B Influence Of Concentration For Constant ␤supporting
confidence: 90%
See 3 more Smart Citations
“…This is in correspondence with the results obtained in ͑sub-͒critical flow by Hu and Lips, 8 Janssen et al, 10,13 Eggleton et al, 12 and Velankar et al 14 It remains to be seen, however, whether this should be attributed to the change in ‫*⌫ץ/*ץ‬ around the reference concentration, or due to the proximity of ⌫ ϱ * . Therefore, these cases will be considered separately.…”
Section: B Influence Of Concentration For Constant ␤supporting
confidence: 90%
“…In general, the influence of the Péclet number on the droplet deformation in supercritical flows ͑Caϭ0.1͒ was found to be similar to its influence on the droplet deformation in subcritical flows. Following Eggleton et al, 12 we investigated the influence of the surfactant coverage on the deformation of a droplet covered with a surfactant described by the Langmuir equation of state with ␤ϭ0.2. Similar to the results obtained by Eggleton et al 12 in subcritical flow, the droplet deformation was found to increase with increasing surfactant coverage ⌫ r /⌫ ϱ for low and moderate ⌫ r /⌫ ϱ .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this limiting case, the interface velocity can be calculated with a boundary integral method. 27,28 Boundary integral methods have been used successfully to study drop dynamics in bulk flow conditions [29][30][31][32][33] or the movement of solid spheres and more recently drops between parallel walls. [34][35][36] In the boundary integral formulation, the velocity u at a point x 0 on the interface is given by…”
Section: A Mathematical Formulationmentioning
confidence: 99%